Peran Mediasi Pelatihan Pada Kompetensi Pegawai Terhadap Kinerja Pada Dinas Perdagangan Dan Perindustrian Kabupaten Bengkalis - Marliya Marliya; Richa Afriana Munthe; Susandri Susandri (New Economy, 2025)
This study aims to Analyze the Influence of Competence on Performance through Employee Training at the Bengkalis Regency Trade and Industry Service. The research method used is quantitative research. all ASN employees of the Bengkalis Regency Trade and Industry Service totaling 58 people and sampling was carried out using census techniques. The data collection technique used was a structured questionnaire. The instrument testing technique in this study was the validity and reliability test using PLS (Partial Least Square) as its measurement. The results of this study indicate that Competence and training have a significant effect on employee performance. Competence also has a significant effect on employee training. In addition, Competence also has a positive effect on employee performance mediated by training.